An Intelligent Diagnostic System for Thyroid-Associated Ophthalmopathy Based on Facial Images - Huang, Xiao; Ju, Lie; Li, Jian; He, Linfeng; Tong, Fei; Liu, Siyu; Li, Pan; Zhang, Yun; Wang, Xin; Yang, Zhiwen; Xiong, Jianhao; Wang, Lin; et al. (Frontiers in Medicine, 2022)
Background: Thyroid-associated ophthalmopathy (TAO) is one of the most common orbital diseases that seriously threatens visual function and significantly affects patients’ appearances, rendering them unable to work. This study established an intelligent diagnostic system for TAO based on facial images. Methods: Patient images and data were obtained from medical records of patients with TAO who visited Shanghai Changzheng Hospital from 2013 to 2018. Eyelid retraction, ocular dyskinesia, conjunctival congestion, and other signs were noted on the images. Patients were classified according to the types, stages, and grades of TAO based on the diagnostic criteria. The diagnostic system consisted of multiple task-specific models. Results: The intelligent diagnostic system accurately diagnosed TAO in three stages. The built-in models pre-processed the facial images and diagnosed multiple TAO signs, with average areas under the receiver operating characteristic curves exceeding 0.85 (F1 score > 0.80). Conclusions: The intelligent diagnostic system introduced in this study accurately identified several common signs of TAO.